PENATAAN KEWENANGAN PEMERINTAH DAERAH BIDANG PERTANAHAN DI MASA MENDATANG - Herry, Musleh (De Jure: Jurnal Hukum dan Syari'ah, 2014)
Making a policy (regelgeving) is one of the functions of government. The fact that all citizens are  always  in contact with the  public policy  issued  by  governments, particularly concerning public interest. The development of the concept of state right to control the land started  from  the constitution which is then poured in the Agraria Law. Tenure by the State is not only done by the central government, but also by the local government  through a process of devolution of authority  in line with  the spirit of  regional  autonomy laws. However, with the issuance of Government Regulation No. 38 of 2007,  the fact that majority of  the state's power in land  still held by the central government on behalf of  the state. This realitiy shows  that the governenment failed  to establish a decentralized system in the land sector.